Ta’zir Terhadap Pencurian di Bawah Nisab Dalam Fiqh Jinayah Menurut Imam Al-Nawawi - Ahmadul Abrar; Jufri Yahya (Siyasah Wa Qanuniyah, 2024)
Theft that necessitates the hudud punishment is theft that has reached a specific minimum threshold, known as nisab. In contrast, for cases of theft that do not reach the nisab threshold, the hudud punishment is not applied; instead, the perpetrator is subjected to ta’zir punishment. Based on the background of the issue, the researcher identified two main research questions: (1) What are the criteria for theft below the nisab that are subject to ta’zir punishment according to Imam al-Nawawi? (2) How is the implementation of ta’zir punishment for theft below the nisab carried out according to Imam al-Nawawi? This study employs a qualitative approach with a documentation method that utilizes documents as the primary source for obtaining information relevant to the research and uses content analysis as the data analysis technique. The research results indicate that (1) Imam al-Nawawi explains specific criteria for both the thief and the stolen goods. For the thief, Imam al-Nawawi states that the thief must be of legal age (baligh), commit the theft voluntarily, have received Islamic teachings, and be under Islamic law jurisdiction. Regarding the stolen goods, this study focuses on the nisab threshold, which is ¼ dinar or 3 dirhams, equivalent in modern terms to approximately 1.0625 grams of gold. (2) As for the implementation of ta’zir punishment for theft below the nisab, according to Imam al-Nawawi, it includes imprisonment for a duration determined by the ruler, lashes, slaps, and reprimands. It is important to emphasize that the punishment must not be excessively severe (ghairu mubarrih).